Types of gambling: finnish gambling narratives under the lens of systems theory - Egerer, Michael (Frontiers in Sociology, 2023)
There seems to be no shortage of gambling and problem gambling typologies. At a closer look, however, previous research identified types of (problem) gamblers and not types of (problem) gambling. While typologies of gamblers are important for developing treatment, these typologies are less useful for harm prevention. The current study uses a system theoretical approach to inquire the gambling communication in order to develop genuine types of gambling.Snowball sampling of Finnish gamblers resulted in 56 participants, who wrote 48 narratives about their ordinary gambling, 43 narratives about their most remarkable gambling event, and 28 about their worst gambling experience. The approach is informed by systems theory: communication on gambling is understood as a result of the reduction of contingency. Rather than focusing on the meaning of gambling or why people gamble, the analysis inquires what is included and what is excluded to make gambling discussable, i.e., the contextures of gambling.An economic as well as a family/intimate contexture were the most prominent. The latter appeared most often in the most memorable gambling experiences. The economic contexture was more common in narrating ordinary and worst gambling situations. In all, four types of gambling could be identified: genuine monetary gambling, resonating monetary gambling, commensal gambling, and liminal gambling.When comparing the previously identified types of gamblers with the types of gambling discovered in the present study, it becomes obvious that a shift from the gamblers, their background, their personality, and their motives to the gambling activity, provides novel insights. The constant appearance of the familial/intimate dimension in the narratives, indicate that beside the financial harms, also societal harms need to be treated as a category of harm in its own right, and not as a consequence of personality disorders, psychological distress, or social deprivation.